Consensus and controversy in the discipline of invasion science. Issue 5 (30th August 2022) - Shackleton, Ross T.; Vimercati, Giovanni; Probert, Anna F.; Bacher, Sven; Kull, Christian A.; Novoa, Ana
Abstract: Approaches, values, and perceptions in invasion science are highly dynamic, and like in other disciplines, views among different people can diverge. This has led to debate in the field specifically surrounding the core themes of values, management, impacts, and terminology. Considering these debates, we surveyed 698 scientists and practitioners globally to assess levels of polarization (opposing views) on core and contentious topics. The survey was distributed online (via Google Forms) and promoted through listservs and social media. Although there were generally high levels of consensus among respondents, there was some polarization (scores of ≥0.39 [top quartile]). Relating to values, there was high polarization regarding claims of invasive species denialism, whether invasive species contribute to biodiversity, and how biodiversity reporting should be conducted. With regard to management, there were polarized views on banning the commercial use of beneficial invasive species, the extent to which stakeholders' perceptions should influence management, whether invasive species use alone is an appropriate control strategy, and whether eradication of invasive plants is possible. For impacts, there was high polarization concerning whether invasive species drive or are a side effect of degradation and whether invasive species benefits are understated. For terminology, polarized views related to defining invasive species based only on spread, whether species can be labeled as invasive in their native ranges, and whether language used is too xenophobic. Factor and regression analysis revealed that views were particularly divergent between people working on different invasive taxa (plants and mammals) and in different disciplines (between biologists and social scientists), between academics and practitioners, and between world regions (between Africa and the Global North). Unlike in other studies, age and gender had a limited influence on response patterns. Better integration globally and between disciplines, taxa, and sectors (e.g., academic vs. practitioners) could help build broader understanding and consensus. Resumen: Los enfoques, valores y percepciones en el campo de las invasiones biológicas son muy dinámicos, y como en otras disciplinas científicas, los expertos pueden tener distintas opiniones. Esto ha creado debates, especialmente sobre temas relacionados con valores, gestión, impactos y terminología. Considerando estos debates, encuestamos a 698 científicos y gestores de todo el mundo para evaluar sus niveles de polarización (opiniones opuestas) sobre una serie de temas fundamentales y polémicos. La encuesta fue distribuida a través de internet (a través de Google Forms) y promovida por medio de listas de correo electrónico y redes sociales. Aunque, en general, hubo consenso entre los encuestados, hubo cierta polarización (puntuaciones de ≥ 0.39 [cuartil más alto]). En relación con valores, hubo una gran polarización sobre aquellas declaraciones relacionadas con el negacionismo de especies invasoras, si las especies invasoras contribuyen a aumentar la biodiversidad y cómo se deberían llevar a cabo los informes sobre biodiversidad. En relación con la gestión, hubo opiniones polarizadas sobre la prohibición del uso comercial de especies invasoras beneficiosas, si la opinión de las partes interesadas debería influir en la gestión, si el uso de especies invasoras por sí solo es una estrategia de control adecuada y si la erradicación de plantas invasoras es factible. En cuanto a impactos, hubo gran polarización en cuanto a sí las especies invasoras conducen a o son un efecto lateral de la degradación de ecosistemas y ssi los beneficios de las especies invasoras están subestimados. En cuanto a terminología, encontramos opiniones polarizadas relacionadas con definir especies invasoras exclusivamente en base a su expansión, si las especies se pueden considerar invasoras en sus rangos de distribución nativos y si el lenguaje utilizado en el campo de las invasiones biológicas es xenofóbico. Los análisis factoriales y de regresión revelaron que las opiniones de los expertos encuestados fueron particularmente divergentes entre personas que trabajan con diferentes taxones (plantas y mamíferos) en diferentes disciplinas (entre biólogos y sociólogos), entre científicos y gestores y entre regiones del mundo (entre países de África y del hemisferio Norte). A diferencia de otros estudios, la edad y el género tuvieron una influencia limitada sobre lass respuestas obtenidas. Una mejor integración global y entre disciplinas, taxones y sectores (o. e., investigadores vs. gestores) podría contribuir a alcanzar un mayor entendimiento y consenso.